ANALYSIS OF PERFORMANCE EVALUATION OF THE SOUTH NIAS REGENCY GOVERNMENT REVIEWED FROM FINANCIAL STATEMENT INFORMATION - Purba, Sahala; Laia, Merisa Aguspani; Samosir, Yosafat Renovaldo; Barus, Ike Anggraeni; Sinaga, Lusia Shelomita (JRMA (Jurnal Riset Manajemen dan Akuntansi), 2024)
The objective is to examine the financial performance of local governments from various aspects, including the Regional Financial Independence Index, Regional Financial Dependence Index, Fiscal Decentralization Degree Index, Regional Original Revenue Effectiveness Index, PAD Efficiency Index, Regional Tax Effectiveness Index, Regional Tax Efficiency Index, and Regional Owned Enterprises Contribution Degree Index. This study is a quantitative descriptive study involving the Research Subject of the Financial statements of the Regional Government of South Nias Regency for the period 2013-2022. The results of the index research on regional financial independence have an average value of 2.06%, and can be categorized as still relatively low. The average regional financial dependence is 85.96%, and it can be said that it is still high. The average decentralized ratio is 12.06%, and can be categorized as low. The average effectiveness rate of PAD is 68.02% which is quite high. The average efficiency rate of PAD is 46% which is quite high. The average local tax efficiency rate of 1% is included in the ineffective category. The average local tax efficiency rate of 2% is included in the very good / efficient category. The ratio of BUMD contribution rate shows an average value of 1%, and the contribution received by BUMD is still low.Tujuan untuk mengkaji performa keuangan Pemerintah Daerah dari berbagai aspek, yang meliputi Indeks Kemandirian Keuangan Daerah, Indeks Ketergantungan Keuangan Daerah, Indeks Derajat Desentralisasi Fiskal, Indeks Efektivitas Pendapatan Asli Daerah, Indeks Efisiensi PAD, Indeks Efektivitas Pajak Daerah, Indeks Efisiensi Pajak Daerah, dan Indeks Derajat Kontribusi Badan Usaha Milik Daerah. Studi ini merupakan studi deskriptif kuantitatif yang melibatkan Subjek Penelitian laporan Keuangan pemerintah Daerah Kabupaten Nias Selatan untuk periode Tahun 2013-2022. Hasil penelitian indeks terhadap kemandirian keuangan daerah memiliki nilai rata-rata yakni 2,06%, dan dapat dikategorikan masih tergolong rendah sekali. Rata-rata ketergantungan keuangan daerah sebesar 85,96%, dan dapat dikatakan masih tinggi. Rata-rata rasio desentralisasi sebesar 12,06%, dan dapat dikategorikan rendah. Rata-rata tingkat efektivitas PAD yakni 68,02% yang tergolong cukup tinggi. Rata-rata tingkat efisiensi PAD sebesar 46% yang tergolong cukup tinggi. Rata-rata tingkat efisiensi pajak daerah sebesar 1% termasuk dalam kategori tidak efektif. Rata-rata tingkat efisiensi pajak daerah sebesar 2% termasuk dalam kategori sangat baik/efisien. Rasio tingkat kontribusi BUMD menunjukkan nilai rata-rata sebesar 1%, dan kontribusi yang diterima BUMD masih rendah.